Getting the Joke: Insight during Humor Comprehension – Evidence from an fMRI Study - Tian, Fang; Hou, Yuling; Zhu, Wenfeng; Dietrich, Arne; Zhang, Qinglin; Yang, Wenjing; Chen, Qunlin; Sun, Jiangzhou; Jiang, Qiu; Cao, Guikang (Frontiers in Psychology, 2017)
Abstract: As a high-level cognitive activity, humour comprehension requires incongruity detection and incongruity resolution, which then elicits an insight moment. The purpose of the study was to explore the neural basis of humour comprehension, particularly the moment of insight, by using both characters and language-free cartoons in a functional magnetic resonance imaging (fMRI) study. The results showed that insight involving jokes elicited greater activation in language and semantic-related brain regions as well as a variety of additional regions, such as the superior frontal gyrus (SFG), the inferior frontal gyrus (IFG), the middle temporal gyrus (MTG), the superior temporal gyrus (STG), the temporoparietal junctions (TPJ), the hippocampus and visual areas. These findings indicate that the MTG might play a role in incongruity detection, while the SFG, IFG and the TPJ might be involved in incongruity detection. The passive insight event elicited by jokes appears to be mediated by a limited number of brain areas. Our study showed that the brain regions associated with humour comprehension were not affected by the type of stimuli and that humour and insight shared common brain areas. These results indicate that one experiences a feeling of insight during humour comprehension, which contributes to the understanding of humour comprehension. Key words:insight, humour comprehension, incongruity-resolution theory, character, language-free cartoon, functional magnetic resonance imaging (fMRI)